Two new earthworm species of the genus Drawida (Oligochaeta: Moniligastridae) from southwestern Taiwan - Shen, Huei-Ping; Chang, Chih-Han; Chih, Wen-Jay (Zootaxa, 2018)
This study describes two new species of earthworms belonging to the genus Drawida (Oligochaeta: Moniligastridae) from southwestern Taiwan. They are Drawida alishanensis sp. nov. and Drawida fenqihuensis sp. nov. The two species were found at elevations of 1407–1661 m in the Alishan area, Chiayi County. DNA barcodes from type specimens of the new species are reported. This is the first time that new species of Drawida are discovered from the island of Taiwan. In addition, Drawida keikiensis Kobayashi, 1938 from Korea is found to be synonymous with Drawida syringa Chen, 1933 from central China. The synonymy of Drawida glabella Chen, 1938 with Drawida barwelli (Beddard, 1886) is rejected.